Jacko Hendrik Ayub Bullan's Sasando Akustik Elektrik as a Cultural Dissemination (Catharsis, 2022)
This research focuses on the Sasando Acoustic Electric instrument developed by Jacob as a cultural transfer strategy. The aim of this research is to demonstrate that Sasando is a part of the cultural heritage of the Rote Island community, and Jacob, as an artist, plays an important role in the development of the instrument. Sasando Acoustic Electric was created as an effort to preserve culture while maintaining its traditional characteristics, yet also able to adapt to the changing times. This musical instrument has become popular and is used for various purposes, including performances, beginners, and courses. Therefore, the researcher chose to investigate Jacob's Sasando Acoustic Electric instrument as one strategy for cultural transfer.The research method used a qualitative approach, using a case study design that analyzed the phenomena that occurred. Qualitative research is considered appropriate for exploring art phenomena. Data analysis in this study went through three stages, namely data collection, data reduction, and data presentation, using the Interactive Model for Qualitative Research by Miles and Huberman. To maintain data credibility, data triangulation and theory were employed. Data was collected through observation, interviews, and document study.The results of this study show that Jacob's Sasando Acoustic Electric is an innovation that successfully transfers traditional culture into a modern form. As an artist, Jacob was able to maintain the traditional characteristics of Sasando while also adapting to the changing times by adding acoustic and electric elements to the instrument. The results of this study can also contribute to the development of traditional culture and art in Indonesia.